Icon as a Method of Choice for Injectable Treatment of Initial Caries in Patients with Fibrodysplasia Ossificans Progressive: a Clinical Case - Svetlana Danshina (Journal of Global Pharma Technology, 2020)
The method considered in this clinical case makes it possible to treat the initial stages of the carious process in patients who are contraindicated by local injection anesthesia. The purpose of this study is to identify opportunities for treating the early stages of the carious process using ICON technology, without the use of injection methods of anesthesia, in patients who were diagnosed with Fibrodysplasia ossificans progressive (FOP). Conclusions: Patients were treated with infiltration of polymer material, without the use of injection methods of anesthesia. The result of this clinical case showed the effectiveness of this technique for patients diagnosed with FOP.Keywords: Fibrodysplasia ossificans progressiva (FOP), Painless, Icon, Carious process, Genetic diseases.